Beasts of the southern wild [videorecording (DVD)] - Zeitlin, Benh; Wallis, Quvenzhané. 2003-; Henry, Dwight; Easterly, Levy (20th Century Fox Home Entertainment, 2012)
Hushpuppy is a six-year-old living in an isolated bayou community. When her father Wink becomes ill, she sets off for the outside world in an attempt to help him. The journey to save her father is delayed by a 'busted' universe that reverses weather patterns and brings about long-extinct animals. Can Hushpuppy save the day? Bonus features include the making of Beasts of the Southern Wild and the theatrical trailer.